The Role of Innovative Decisions in the Development of Oil and Gas Companies - Andronova, Irina Vladimirovna; Osinovskaya, Irina Vladimirovna (International Journal of Energy Economics and Policy, 2017)
This work describes the importance of developing and adopting innovative decisions in all operational segments of O&G companies. It gives a systematic presentation of the procedure of developing and making managerial decisions of an innovative nature that have a multilevel structure. A special place in the hierarchy of innovative decisions is given to the ones adopted to implement innovative foresight projects targeted to possible technological breakthroughs that can have a significant impact on the development and growth of key indicators in various operating segments of O&G companies. It also emphasizes the need to develop company innovative potential based on its staff. It is the staff with innovative habit of thought that can ensure the high efficiency of preparation and implementation of innovative decisions. The main requirements for innovators are also described herein below. Moreover, the problem of special training of this group (innovators) is touched on. One of the possible solutions of this problem is to develop the appropriate corporate training. Keywords: innovative decisions, foresight, algorithm, personnel, innovative potential, corporate training. JEL Classifications: J24, O31